A mysterious Ottoman narration :|Hagop Haciyan’s Kış Geceleri as a 19th century adventure novel - Çelik, Azra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This thesis examines Agop Haciyan's Kış Geceleri as an example of an adventure novel sub-genre classified as a popular novel genre. Written in the 19th century Ottoman Empire, the work was originally written in Armenian under the name of "Pera Geceleri" and then transferred to Turkish with some changes and became popular enough to make three editions in its period. The text, which is about the adventures of the Armenians in the Beyoğlu region, is generically related to the Paris Mystery text. Continuing the "mysterious revenge adventures" genre, of which Paris Mystery is the founding text, Kış Geceleri has created a variation in this genre in the context of Ottoman literature. When we look at the common features of mysterious vengeance adventures, the text mostly walks in the heart of a city with the emergence of a situation to take revenge due to a crime and the deterioration of the existing order, ending with the restoration of justice. At the end of the adventure, the super strong heroes restore order by applying justice in their way, and take revenge on the weak, and close the text. However, the text of Kış Geceleri ends with the inability to take revenge, the victims of the text turn into madness, and the establishment of justice by the state, which cannot be established by the heroes. In this way, the text creates a kind of deviation.
Keywords: Adventure stories.